Activation of the Elderly in an Urban Environment as a Form of Counteracting Social Exclusion - Majer, Ryszard (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The process of social exclusion influences especially the dynamically aging Polish society, particularly elderly persons living in an urban environment. There are many factors influencing the exclusion from the society, which include: the economic, health and living environment factors. Social inclusion of the seniors should be conducted on all levels of the social policy, however the most important role should be played by the local governments. Only on the local level it is possible to recognize the reasons for social exclusion and create a system in which a number of entities will include the eldest citizens to the society by way of a process of social activation. The process of activation should be programmed, realized and monitored, because only then it will become a successful process which will create a real chance to counteract social exclusion or seniors, in the introduction to the article, the author presents the theoretical aspects of social exclusion and the goals of the inclusion process. In the part devoted to the abilities of influencing social policies by the local government, the author presents an example of Częstochowa as a city that has created a senior aid program. In the third part of the article the author presents the results of the studies based on the monographic sheets of the Senior Initiative Bank, according to which, the range of the activation activities for the local senior society can be evaluated.